Post-chornobyl remote radiation effects on human sperm and seminal plasma characteristics - Andreychenko, S.V.; Klepko, A.V.; Gorban, L.V.; Motryna, O.A.; Grubska, L.V.; Trofimenko, O.V. (Experimental Oncology, 2016)
Aim: The research was aimed on analysis of the remote consequences of Chornobyl accident on the reproductive function of men adult residing in Ukraine. Materials and Methods: 232 male volunteers with mean age of 34 years (range 20–47) from 5 different regions of Ukraine (Zhytomyr, Ivano-Frankivsk, Kyiv, Poltava, and Kyiv city) were enrolled in cross-sectional studies of long term radiation effects on seminal plasma and sperm. All manipulations, analysis and classification of ejaculates were done accordingly to WHO recommendations. The content of neutral α-glucosidase, fructose, citric acid in the seminal plasma was determined by spectrophotometry, L-carnitine — by high performance liquid chromatography, zinc — by atomic absorption spectroscopy. Results: In the men residing in the regions heavily contaminated with radioonuclides, the decreased sperm quality with concurrent asthenozoospermia, oligozoospermia, teratozoospermia, asthenoteratozoospermia, oligoasthenoteratozoospermia and oligoteratozoospermia was revealed. Moreover, the concomitant shifts in seminal plasma content of neutral α-glucosidase, fructose, citric acid, L-carnitine and zinc were detected. Conclusion: The study has revealed the ample sperm and semen abnormalities amongst the inhabitants of radiation polluted territories that should have to be a subject of careful research in forthcoming years. This article is a part of a Special Issue entitled “The Chornobyl Nuclear Accident: Thirty Years After”.